PENGARUH KINERJA BERBASIS PENCIPTAAN NILAI DAN VARIABEL MAKROEKONOMI TERHADAP RETURN SAHAM INDUSTRI PAKAN TERNAK - Karmilah, Evi; Nurmalina, Rita; Setiawan, Budi (Jurnal Manajemen dan Agribisnis, 2016)
The creation of value-based performance measurement can be an alternative in measuring the company's financial performance. Results can be used as indicators of assessments by investors, and these indicators can influence the stock returns. Besides, macroeconomic variables also affect stock returns. This study aimed to analyze the financial performance of companies in the process of creation of value-added with EVA, MVA, and Tobin's Q approach. Impacts of these performance measurements and macroeconomic variables (exchange rates, interest rates, and inflation) on stock returns of the subsector animal feed industry were studied. Descriptive analysis was applied in analyzing the company's financial performance. The impacts of the company financial performance and macroeconomic variables were assessed by using panel data regression analysis. The results related to the company's performance showed that 1) EVA performance dominantly obtained a positive EVA value; 2) MVA performance predominantly produced a positive MVA value in 3 companies and a negative MVA value in the other company; 3) Tobin’s Q performance predominantly generated a value of Q>1 in 2 companies and a value of Q